2014
DOI: 10.1177/070674371405900606
|View full text |Cite
|
Sign up to set email alerts
|

The McGill Geriatric Lithium-Induced Diabetes Insipidus Clinical Study (McGLIDICS)

Abstract: The prevalence of decreased UOsm is similar in geriatric and adult lithium users, but older patients are less likely to report urinary and thirst symptoms. Although subjective symptoms do not correlate with UOsm, USG may be a cost-efficient clinical surrogate measure for UOsm. We suggest clinicians increase their vigilance for decreased UOsm, especially in lithium users with advanced age, longer duration of lithium exposure, and higher lithium levels. This may potentially prevent lithium intoxication, falls, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…McGLIDICS (the McGill Geriatric Lithium-Induced Diabetes Insipidus Clinical Study) [15] was a cross-sectional study of 100 geriatric (age C65 years) and adult (age 18-64 years) outpatients with current or previous lithium exposure. Between 25 May 2011 and 28 August 2012, 103 consecutive outpatients were recruited at four geriatric psychiatry clinics and two adult mood disorder clinics affiliated with McGill University (Montreal, QC, Canada) and University of Toronto (Toronto, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…McGLIDICS (the McGill Geriatric Lithium-Induced Diabetes Insipidus Clinical Study) [15] was a cross-sectional study of 100 geriatric (age C65 years) and adult (age 18-64 years) outpatients with current or previous lithium exposure. Between 25 May 2011 and 28 August 2012, 103 consecutive outpatients were recruited at four geriatric psychiatry clinics and two adult mood disorder clinics affiliated with McGill University (Montreal, QC, Canada) and University of Toronto (Toronto, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that statins increase AQP2 abundance at the apical plasma membrane of CD principal cells in vivo in a mouse model of genetically induced NDI. 3 The preliminary data presented in the Letter by Elie et al 4 unambiguously showed that statins attenuate the drop in urine osmolality, observed also in Li þ -induced NDI. They showed that none of the statin users observed in their study had urine osmolality o300 mOsm/kg during Li þ treatment.…”
mentioning
confidence: 89%
“…We used cross-sectional data from 71 lithium users enrolled in the McGLIDICS study. 4 We analyzed the correlation between statin use and urine osmolality, including multivariate analyses controlling for age, lithium level, and duration. 4 Patients were aged 20-95 years (mean 60.9), 54.9% were female, 88.6% had bipolar disorder, and mean lithium duration and serum level were 10.6 years and 0.62 mmol/l, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] Li is interesting because this small cation competes with Na for translocation across cell membranes via the Na pump, the Na channel, and Na cotransporters, in both kidney and choroid plexus. 16,17 As a result, Li therapy, which is effective in controlling bipolar disease in adults and children, 18 in some cases may be problematic in perturbing body fluid balance, 19 including the extracellular fluids and barriers of the brain and CSF. 20 Therefore, using choroid plexus transport modeling, 1,6 we seek to inform on a link between Li-carbonate (i.e., Li 2 CO 3) therapy, stimulated choroid plexus transport of Na, greater CSF formation, and the augmented ICP in PTCS of both adult and pediatric patients.…”
Section: Introductionmentioning
confidence: 99%